2020
DOI: 10.12688/f1000research.22311.2
|View full text |Cite
|
Sign up to set email alerts
|

The benefit of cinnamon (Cinnamomum burmannii) in lowering total cholesterol levels after consumption of high-fat containing foods in white mice (Mus musculus) models

Abstract: Background: Hypercholesterolemia is a condition where cholesterol levels in the body exceed the normal range. If the condition is longer, it can cause metabolic and cardiovascular diseases. The therapy of synthetic drugs has side effects that can be fatal (rhabdomyolysis). Needed to find natural remedies with minimal side effects. There are many nutritional components contained in cinnamon, such as cinnamaldehyde. The cinnamaldehyde, a substance that is thought to affect cholesterol levels. The study aims to d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 11 publications
0
2
0
1
Order By: Relevance
“…In addition to Chinese cassia, other varieties of cinnamon have also been found to improve lipid metabolism. In hypercholesterolemia mice model induced by quail yolk, TC content in serum decreased after administration of cinnamon (Cinnamomum burmannii) for 28 days [41]. Similarly, cinnamon (Cinnamomum zeylanicum) bark extract supplement can reduce the blood levels of TC and TG in hyperlipidemia albino rats induced by Triton X-100 injection [42].…”
Section: Cinnamomi Cortex (Rougui)mentioning
confidence: 99%
“…In addition to Chinese cassia, other varieties of cinnamon have also been found to improve lipid metabolism. In hypercholesterolemia mice model induced by quail yolk, TC content in serum decreased after administration of cinnamon (Cinnamomum burmannii) for 28 days [41]. Similarly, cinnamon (Cinnamomum zeylanicum) bark extract supplement can reduce the blood levels of TC and TG in hyperlipidemia albino rats induced by Triton X-100 injection [42].…”
Section: Cinnamomi Cortex (Rougui)mentioning
confidence: 99%
“…A meta-analysis that included 23 studies (1,070 subjects) concluded that there was no association between cinnamon consumption and differences in LDL-cholesterol, high-density lipoprotein cholesterol, and HbA1c levels. Studies on cinnamon in vitro, in animals, and in humans are listed in Table 5 [9,45,[131][132][133][134][135][136][137][138][139][140][141][142][143][144]. Again, allowance for different exposome features, such as microbiota composition, may be pertinent here [145].…”
Section: Cinnamon and Cardiovascular Diseasementioning
confidence: 99%
“…Beberapa obat penurun kolesterol bekerja pada proses metabolisme kolesterol yang terjadi di liver seperti statin, dengan cara menghambat kerja enzim HMGCoA sehingga pembentukan kolesterol terhambat (Vujkovic, 2024;Würtz et al, 2016). Terdapat juga obat yang bekerja pada proses penyerapan kolesterol pada usus halus dengan menghambat protein Niemann-Pick C1-like 1, seperti Ezetimebe (Wang et al, 2023) (Alsoodeeri et al, 2020;Pane & Pulungan, 2020). Hipotesa yang mendukung hasil penelitian tersebut berupa, aksi lipolitik kayu manis dari senyawa sinamaldehid.…”
unclassified